An optimized protocol for expression and purification of monomeric full-length BAX protein for functional interrogations - Chen, Yiyang; Gelles, Jesse D.; Mohammed, Jarvier N.; Chipuk, Jerry Edward (Frontiers in Cell and Developmental Biology, 2023)
Diverse developmental signals and pro-death stresses converge on regulation of the mitochondrial pathway of apoptosis. BAX, a pro-apoptotic BCL-2 effector, directly forms proteolipid pores in the outer mitochondrial member to activate the mitochondrial pathway of apoptosis. BAX is a viable pharmacological target for various human diseases and increasing efforts have been made to study the molecular regulation of BAX while identifying small molecules selectively targeting BAX. However, generating large quantities of monomeric and functionally competent BAX has been challenging due to its aggregation-prone nature. Additionally, there is a lack of detailed and instructional protocols available for investigators who are not already familiar with recombinant BAX production. Here, we present a comprehensive protocol for expressing, purifying, and storing functional monomeric recombinant BAX protein. We utilize an intein-chitin binding domain-tagged BAX construct and employ a two-step chromatography strategy to capture and purify BAX, along with providing example standard assays to observe BAX activation. We also highlight best practices for handling and storing BAX to effectively preserve its quality, shelf-life, and function.